Assessing Staphylococcus aureus in ready-to-eat food and sanitation level of food premises in Putrajaya, Malaysia - Abdul Wahab, Shafizi (2016)
Food and waterborne diseases especially food poisoning cases are still a problem in public health. The incidence happened due to unsanitary food premise and unhygienic food handlers practice during food handling. Therefore, the information of food safety and sanitation of food premises is crucial in planning strategies to prevent or reduce the incidence of food poisoning cases. A cross sectional study was conducted with the objective of the study were to determine the presence of Staphylococcus aureus in ready-to-eat (RTE) food, assessing the level of sanitation of food premises and determining the association between the presence of S. aureus in RTE food and the level of sanitation of food premises in Putrajaya, Malaysia. Method of most probable number (MPN) and polymerase chain reaction (PCR) were combined in this study to determine the number of S. aureus in RTE food. A total of 106 samples of RTE food were purchased from 53 food premises have been analyzed and the results confirmed by 56 (53%) samples contained S. aureus meanwhile the rest 50 (47%) not detected presence of S. aureus. Analyzed also show RTE food cooked detected S. aureus by 50 (45%) of the samples compared to RTE food that is still raw with the number 56 (55%). As for assessment, the assessment form has nine (9) main parameters consisting of 40 variables as a basis, was conducted on 53 of food premises to determine the level of sanitation of the premises. The pre-test to the assessment form was implemented to 10 food premises in Kuala Lumpur beforehand and the result was a practical and consistent for use in research. The results of the assessment carried out revealed a total of 49 (92%) were in a state of sanitary premises, and the remaining 4 (8%) were categorized as unsanitary premises. In terms of risk level, a total of 4 (8%) were high risk premises, 26 (49%) moderate risk, and the remaining 23 (43%) were at low risk. The study also found no significant association between the presence of S. aureus in RTE food with the level of sanitation of food premises in Putrajaya.